THE APPLICATION OF WARM WATER COMPRESSES WITH GINGER AND LEMONGRASS ON PAIN INTENSITY IN PATIENTS WITH GOUT ARTHRITIS - Susanti, Susanti; Andriani, Dwi; Bistara, Difran Nobel (Nurse and Holistic Care, 2021)
Background: Arthritis Gout or Gout is also a category of chronic non-communicable disease (NCD). Gout is a metabolic disease caused by excess levels of uric compounds in the body. A Pharmacological approach that can be used is the administration of NSAID drugs. The non-pharmacological approach can be in the form of education, setting a low-purine diet and pain management guidelines using warm compresses to reduce pain gout sufferers and improve or maintain function and quality of life. Objective: To determine the effect of warm water compresses application with pieces of ginger and lemongrass on pain intensity in patients with gout arthritis. Methods: This was a pre-experimental study with one group using pre and post-test approach. The sample was patients with gout arthritis who experienced pain in the joints as many as 25 respondents were selected using simple random sampling. The data analysis was using Wilcoxon Statistical Test. Result: This study was using respondents precentage for pre and post-test, the average respondent experienced moderate pain and after the intervention, the pain intesity decreased to relax and comfortable. Statistical test results showed p-value = 0.000< =0.05, meaning that there was an effect of giving warm water compresses with pieces of ginger and lemongrass on the pain intensity of means that it had an impact on pain intensity in people with gout. Conclusion: This result showed that the application of warm water compresses with pieces of ginger and lemongrass could lowering the pain intensity in people with gout.